Implications of parental deployment for Army National Guard and Army Reserve families: practitioners’ role in supporting adolescents - Richmond, Chelsea Lee (Kansas State University, 2011)
Since the September 11th, 2001, terrorist attacks on the United States, a large number of service members have deployed multiple times to active combat zones as a result of U.S. involvement in the global war on terrorism. Army National Guard and Army Reserve families may find these deployments challenging as they are often isolated by living in civilian communities and have limited access to military support services and networks. Adolescents who live in these families may be particularly vulnerable as the stressors of parental deployment are layered on top of the normative stressors of adolescent development. This report will examine the challenges that adolescents and their families experience as a result of parental deployment. Additionally, protective factors that can help mitigate those challenges will also be discussed. Finally, Bronfenbrenner’s bioecological theory will be used as a framework to identify ways in which parents, schools, communities, and the U.S. Army can support adolescents, thus helping them to positively cope with parental deployment.
Keywords: Adolescence; Parental deployment; Military families; Army National Guard; Army Reserve; Education, General (0515)